Industrial waste inventory and integrated waste management scheme for Cavite Economic Zone - Bansuli, Cielo B. (2004)
The Philippines, is one of the developing countries in Asia that has experienced significant industrial growth in recent years and this has coincided with the establishment of the Philippine Economic Zone Authority (PEZA) in 1995, which in turn gave rise the about ninety-six (96) number of industrial estates in the country. Cavite Economic Zone is the largest of he four government-managed industrial estates operated by PEZA. This industrial estate generated 29 percent of the total exports of the Philippines in 2002. However, the industrial estate generates significant amounts of industrial waste and currently there is no centralized waste management program. The Ecological and Solid Waste Management Act (RA 9003) and the Toxic Substances and Hazardous Waste Management Act (RA 6969) of the Philippines require that solid waste and treated hazardous waste is disposed in a landfill while the Clean Air Act (RA 6749) bans the use of incinerators for such waste. Currently, there is no available landfill in the Province of Cavite or in its surrounding area. Also, while there are a number of environmental service providers, the services provided by these companies are inadequate of expensive. The integration of waste management schemes, which is possible in an industrial estate, has the potential to help solve some of the abovementioned problems by ensuring efficient waste management in relatively economic terms. To achieve this, the following specific objectives are to be undertaken: 1. To determine the total quantity and characteristics of the non-hazardous solid waste generated at the industrial estate. 2. To establish a waste flow alternative that will maximize the potential for resource recovery from the waste. 3. To identify the basic components for a centralized waste recovery, treatment and disposal facility. A waste survey was designed in order to obtain data in relation to waste type and volume generated by locators within the industrial estate as reported by locators, garbage collectors and hazardous waste treaters over the three-month period comprising June to August 2001. The waste survey was issued to the different respondents by the administration office of the industrial estate and this ensured a one-hundred percent response rate.